An experimental assessment of the efficiency of glazing types used as cladding materials for multi-storey office buildings in Ghana - Koranteng, C.; Nkrumah, J.; Essel, C. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Architecture all over the world in recent years has embraced the extensive use of glass as a cladding material for high-rise structures. Multi-storey structures in Ghana have seen it fair share in this growing phenomenon. Experimental results on the effectiveness of the glazing types used for the cladding is presented and discussed in this work. The aim of the study was to establish the effectiveness of the glazing types towards the reduction of thermal discomfort and cooling loads in high rise office buildings in Accra, Ghana. The simulation technique with the use of the Tas simulation tool was used in this study. The methodology used was the case-study, where a multi-storey structure was selected and used in the running of the experiment. The analysis showed that in terms of cooling loads, the single glazing performed poorly. Though the triple glazing was the best, economically, the double glazing could be used instead. In terms of solar gains, the single glazing again was the poorest. It is recommended that the selection of a glazing type for any multi-storey structure should be done after an elaborate simulation. This will help in the determination of the total cooling loads for the building in order to reduce the extensive use of energy which has become one of the scarcest commodities in Ghana at the moment.